Unknown aspect of the old disease: does dyslipidemia in systemic AA amyloidosis differ from the dyslipidemia in primary glomerulonephritis?. (14th September 2015) - Piskinpasa, Serhan; Agbaht, Kemal; Akoglu, Hadim; Akyel, Fatma; Ozkayar, Nihal; Yenigun Coskun, Ezgi; Turgut, Didem; Koc, Eyup; Odabas, Ali Riza; Dede, Fatih
Abstract: Aim : To investigate the nature of dyslipidemia and its diversity in patients with systemic AA amyloidosis. Methods : The reports of the kidney biopsies performed due to nephrotic proteinuria (>3.5 g/day/1.73 m 2 ) with preserved renal function [glomerular filtration rate (GFR) >60 mL/min/1.73 m 2 ] were reviewed. Clinical and laboratory data of the patients with systemic AA amyloidosis and primary glomerulonephritis (PG) were analyzed. Results : A total of 104 (systemic AA amyloidosis: 43, PG: 61) patients were included in the study. Proteinuria and GFR levels were similar in both the groups. Patients with systemic AA amyloidosis group had lower serum albumin ( p  = 0.002), lower hemoglobin levels ( p  = 0.001), higher platelet counts ( p  = 0.002) and higher C-reactive protein levels ( p  = 0.001) compared to patients in PG group. Although the frequency of dyslipidemia was similar in the groups (86.0 vs. 93.4%), patients with systemic amyloidosis had both lower values of LDL-C (4.56 ± 2.05 vs. 5.49 ± 2.23 mmol/L, p  = 0.028) and HDL-C (1.19 ± 0.36 vs. 1.35 ± 0.39 mmol/L, p  = 0.035). Serum lipid levels were correlated with serum total protein, albumin and proteinuria levels in PG group. However, in the systemic amyloidosis group, only one clear correlation between serum lipid and hemoglobin levels was estimated. A multivariate analysis demonstrated that LDL-C was independently associated with the etiology of nephrotic proteinuria, serum total protein, serum albumin (inversely) and hemoglobin levels. Conclusions : Although dyslipidemia is closely associated with serum total protein, albumin and proteinuria in patients with PG, there is no clear such association in patients with systemic amyloidosis. Correlation between serum lipid and hemoglobin levels in this group and other findings point out that probably complex mechanisms take place in dyslipidemia of nephrotic syndrome caused by systemic AA amyloidosis.